EFEKTIVITAS PELAKSANAAN PROGRAM SEMBAKO MASA PANDEMI COVID-19 DI DESA PARDAMEAN SIBISA KECAMATAN AJIBATA - Sirait, Intan Novena (JOURNAL OF SOCIAL, JUSTICE AND POLICY, 2022)
Human needs include clothing, food, and shelter. Meeting these needs must do the work because with the increasing needs. Indonesia is one of the countries that face problems of poverty and food insecurity, generally because many people have low incomes. In tackling poverty, the government issued several policies, including one of them is food social assistance, known as the basic food program. Food social assistance has undergone several transformations. In 2020, in order to minimize the impact of covid-19, the government made changes to the instruments in the basic food program, namely the expansion of participation, value of benefits and types of commodities. This study aims to describe the effectiveness of the implementation of the basic food program. Using the theory to measure effectiveness proposed (Budiani, 2007) namely target accuracy, socialization program, program objectives and program monitoring. There were 9 informants in this study consisting of 5 Beneficiary Families, 1 assistance assistant, 1 village head and 2 community members who did not receive assistance. The results obtained from this study indicate that the implementation of the basic food program during the covid-19 pandemic has not been effective, as seen from: targeting accuracy is described as less effective, socialization is described as effective, program objectives are quite effective and monitoring is programless. There are supporting factors in the implementation of this program, namely the availability of e-warong equipped with supporting facilities and the inhibiting factor is that there is only 1 e-warong available for 9 villages and 1 kelurahan with villages that can be said to be quite far from Ajibata District.